Soft \(D_μ\)-Compactness in Soft Generalized Topological Spaces (Journal of Informatics and Mathematical Sciences, 2017)
The aim of this paper is to introduce a further generalization of compactness in soft generalized topological spaces. We define and study the concept of soft \(D_μ\)-compact spaces in soft generalized topological spaces. Basic properties and characterizations of soft \(D_μ\)-compact spaces are established. Soft \(D_μ\)-compactness in subspaces of soft generalized topological spaces are also investigated.
Keywords: Soft generalized topological spaces; Soft \(D_μ\)-set; Soft \(D_μ\)-compactness; Soft \(μ\)-\(D_2\) space